Evaluating protection systems against marine corrosion of aeronautic alloy alclad 2024-t3 (2011)
This paper shows how two coating systems were obtained as an alternative for protection against corrosion of al clad 2024-T3which is used in battery compartment manufacture for T-41 aircraft. Such systems consist of three types of organic resin: a first layer of P-115 polyester resin as the first coating on both systems, and a second layer of Hetron 197-3 polyester resin in the first system and vinyl-ester resin in the second one. Scanning electron microscopy (SEM) was used for surface morphology analysis, showing the roughness produced by surface treatment. The coatings were electrochemically characterised by electro chemical impedance spectroscopy (EIS) and Tafel polarization curves; it was found that both systems had good performance against corrosion in a marine environment and the chemical surface preparation system had a superior protective pattern for Alodine5700 + 197-3 Hetron, a 1.42x10-12mpycorrosion rate being obtained while substratum rate was 1.59x10-7 mpy.